Estandarización de la Rutina de Ordeño de Bovinos en las Unidades Productivas del Cantón Salcedo. - Chanaluisa Unaucho, Jimmy Patricio (2019)
The present research project "Standardization of milking routines (Good Management Practices) of bovines in the productive units of Salcedo Town" has as its primary objective to determine the general characteristics that lead good milk production practices that must be carried out at the moment of carrying out the milking routines in the productive units of Salcedo Town, these correspond to the rural parishes (Antonio José Holguín, Cusubamba, Mulalillo, Mulliquindil, Panzaleo), it is proposed to carry out a process of standardizing the proper milking routines according to the regulations that dairy companies require, which consists of adjusting and controlling the quality of the milk. Currently, dairy production has reached levels of competitiveness that require greater demands for productive efficiency, regardless of the different management conditions or milk exploitation systems, within the obtained results from the rural parishes of Salcedo Town, milk samples and physical-chemical were analyzed and it was interpreted with descriptive statistics, the density which reference range is (1.027-1.033) was demonstrated. ) the 5 rural parishes maintain the range, pH (6,6-6,8) no variation of the ranges, Protein (3,3-3,6) remain in the established range, Non-fat solids (8,5 -9.5) there is no variability, Lactose (12.7), Fat (3.7) maintaining a variability of results due to the different nutrition and genetics of the animal. For this reason, the dairy producer needs to identify the faults or weak points of farming and improve these factors to increase the productive efficiency in daily life. An adequate milking routine is the ideal complement to obtain the highest volume of milk possible from the herd, together with the fundamental pillars of all production such as: the genetic characteristics of the animals, the type of feeding, the quality of the infrastructure and the health care.